2017
DOI: 10.1016/j.ymthe.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA29a Treatment Improves Early Tendon Injury

Abstract: Tendon injuries (tendinopathies) are common in human and equine athletes and characterized by dysregulated collagen matrix, resulting in tendon damage. We have previously demonstrated a functional role for microRNA29a (miR29a) as a post-transcriptional regulator of collagen 3 expression in murine and human tendon injury. Given the translational potential, we designed a randomized, blinded trial to evaluate the potential of a miR29a replacement therapy as a therapeutic option to treat tendinopathy in an equine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 50 publications
1
61
0
2
Order By: Relevance
“…Increased miR-29b led to decreased expression of TFG-B1 and the gliding excursion repaired tendon was increased Watts et al 32 miR-29a Equine Digital flexor tendon miR-29a replacement therapy resulted in downregulation of collagen III expression as well as decreased tendon lesion size versus control MICRO-RNA IN TENDINOPATHY and Col3 expression upon targeting EGR-1, 20 which is similar to the actions of miRNA-29b in collagen fiber inhibition. Micro-RNA-140 also demonstrated multiple functions, with upregulation of TGF-B1 while mediating the reduction in mechanical loading.…”
Section: Watts Et Al Reported Decreasedmentioning
confidence: 87%
See 3 more Smart Citations
“…Increased miR-29b led to decreased expression of TFG-B1 and the gliding excursion repaired tendon was increased Watts et al 32 miR-29a Equine Digital flexor tendon miR-29a replacement therapy resulted in downregulation of collagen III expression as well as decreased tendon lesion size versus control MICRO-RNA IN TENDINOPATHY and Col3 expression upon targeting EGR-1, 20 which is similar to the actions of miRNA-29b in collagen fiber inhibition. Micro-RNA-140 also demonstrated multiple functions, with upregulation of TGF-B1 while mediating the reduction in mechanical loading.…”
Section: Watts Et Al Reported Decreasedmentioning
confidence: 87%
“…Application of miRNA downregulated collagen III but not collagen I Watts et al 32 miR-29a Equine Digital flexor tendon miR-29a replacement therapy decreased collagen III expression 20 miR-217 Human Achilles tendon P16 inhibits tenogenic differentiation of TSPCs, mediated by miR-217 and its target EGR1 Chen et al 18 MiR-135a Rats Achilles tendon…”
Section: Digital Flexor Tendonmentioning
confidence: 99%
See 2 more Smart Citations
“…By controlling interleukin 33 syntheses, miR‐29a positively regulated collagen 3 (Col‐3) expression in tenocytes and miR‐29a downregulation was correlated with the overexpression of Col‐3, resulting in an unbalanced ratio of collagen type 1 and 3, which is a hallmark of tendon degeneration. Further, in an equine therapeutic model Watts et al demonstrated a significant reduction of Col‐3 synthesis by overexpression of miR‐29a, illustrating the important role of miRNAs in fine‐tuning ECM composition in tendon tissue …”
Section: Discussionmentioning
confidence: 98%